2014
DOI: 10.1007/s00430-014-0336-3
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus (HEV) in humans living in high pig density areas of Germany

Abstract: An increase in acute autochthonous hepatitis E virus (HEV) infections has been recorded in Germany. These are suspected to be zoonotically transmitted from wild boar, deer and domestic pig. The latter may represent a major reservoir for HEV. In this study, 537 sera from humans living in Westphalia and Lower Saxony, representing areas of high pig density in Germany, were tested for the presence of HEV-specific antibodies. Among them were 302 individuals with occupational, direct contact to pigs and 235 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 68 publications
3
43
0
4
Order By: Relevance
“…It confirmed that these products represent a source of HEV transmission, particularly in these geographical areas (15). Direct contact with pigs through farming and slaughtering or with wild boars through hunting are other potential risks for the zoonotic transmission of HEV (1,(16)(17)(18)(19)(20). In addition, several studies demonstrated that pigs and wild boars in southern France can be infected with HEV (21,22), and Carpentier et al (23) reported that wild boars from southern France are at higher risk of HEV infection than wild boars from northern France.…”
Section: H Epatitis E Virus (Hev) Genotype 3 Is Endemic In Europe (1-3)mentioning
confidence: 73%
“…It confirmed that these products represent a source of HEV transmission, particularly in these geographical areas (15). Direct contact with pigs through farming and slaughtering or with wild boars through hunting are other potential risks for the zoonotic transmission of HEV (1,(16)(17)(18)(19)(20). In addition, several studies demonstrated that pigs and wild boars in southern France can be infected with HEV (21,22), and Carpentier et al (23) reported that wild boars from southern France are at higher risk of HEV infection than wild boars from northern France.…”
Section: H Epatitis E Virus (Hev) Genotype 3 Is Endemic In Europe (1-3)mentioning
confidence: 73%
“…By the time the animals are transferred to the research campus, most no longer are viremic or shedding the virus, and with good workplace practices, transmission to persons with pig contact will be low. Individuals with close contact to the pigs, such as veterinarians and farm workers, or to pig blood, such as slaughter-house workers and hunters, have been found to have higher rates of anti-HEV than the general population and suggest that close contact with pigs or wild boar is a risk factor for acquiring HEV (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Wyniki badań serologicznych prowadzonych wśród hodowców świń, lekarzy weterynarii oraz pracowników leśnych dowodzą częstszej obecności anty-HEV IgG u osób z tych grup zawodowych. Niemniej jednak nie obserwuje się gwałtownego wzrostu zachorowań osób zawodowo narażonych na kontakt ze zwierzętami (7,27,39,42,64).…”
Section: Replikacja Wirusa W Komórceunclassified
“…w stadach trzody chlewnej w Norwegii (29), USA (88,8%) (69), a także Belgii i Holandii (73%) (2). Niższą częstość infekcji stwierdzano u świń w Niemczech (46,9%), Wielkiej Brytanii (21,5%) i Czechach (5%) (2,27). Zakażenie zwierząt przebiega bezobjawowo z okresowym wydalaniem wirusa w kale.…”
Section: Hev U Trzody Chlewnejunclassified